Systematic Approach to Agroforestry Policies and Practices in Asia - Park, M.S.; Baral, H. (MDPI, 2022)
Agroforestry is an intensive land management system involving the integration of tree management into crop and animal farming. It provides diverse ecosystem services by bridging agriculture, forestry, and husbandry to offer environmental, economic, and social benefits. In order to improve the benefits of agroforestry to meet development and climate goals, a systematic approach is necessary for understanding agroforestry practices, designing agroforestry policies and associated outcomes. Multiple methodologies, including systematic review and landscape restoration approaches, can be applied to analyzing agroforestry policies and ecosystem services derived from agroforestry practices. Therefore, this Special Issue focuses on systematic approaches to agroforestry policies, strategies, and practices. It includes case studies from several countries from Asia to explore economic, social, and environmental dimensions.